2015
DOI: 10.1093/cid/civ051
|View full text |Cite
|
Sign up to set email alerts
|

Use of Clinical and Neuroimaging Characteristics to Distinguish Temporal Lobe Herpes Simplex Encephalitis From Its Mimics

Abstract: In addition to HSE, other infectious and noninfectious etiologies should be considered in the differential diagnosis for TL encephalitis, depending on the presentation. Specific clinical and imaging features may aid in distinguishing HSE from non-HSE causes of TL encephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 30 publications
2
91
1
2
Order By: Relevance
“…As well, involvement of the basal ganglia, thalamus, and (orbital) frontal lobe may appear; our series changes were even bilateral in 53 % of patients (Chow et al 2015;Domingues et al 1998;Oyanguren et al 2013;Sili et al 2014). Our study suggests the superiority of DWI to conventional T2-or FLAIR-weighted MRI in detection of early signal abnormalities in HSVE (Renard et al 2015).…”
Section: Mri Imagingsupporting
confidence: 53%
“…As well, involvement of the basal ganglia, thalamus, and (orbital) frontal lobe may appear; our series changes were even bilateral in 53 % of patients (Chow et al 2015;Domingues et al 1998;Oyanguren et al 2013;Sili et al 2014). Our study suggests the superiority of DWI to conventional T2-or FLAIR-weighted MRI in detection of early signal abnormalities in HSVE (Renard et al 2015).…”
Section: Mri Imagingsupporting
confidence: 53%
“…On the contrary, a recent study of cases of encephalitis with temporal lobe abnormalities found that bilateral temporal lobe involvement was associated with lower odds of HSVE compared with all other etiologies and when directly compared with autoimmune etiologies [84]. In that study of immune competent adults, patients with HSVE, as compared with other infectious or autoimmune etiologies of their temporal lobe encephalitis, were more likely to be older and white, and to present acutely and with fever, seizures, and upper respiratory symptoms.…”
Section: Neuroimagingmentioning
confidence: 83%
“…Chow et al [84] recently reviewed the clinical and neuroimaging features of 251 cases of temporal lobe encephalitis from the California Encephalitis Project. Among all cases of temporal lobe encephalitis, 43 % were infectious and 16 % were noninfectious etiologies.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…However, the constellation of an acute onset, a rapidly worsening short course of a vivid symptomatology can differentiate the prodrome of encephalitis from migraine. In addition to other procedures, the performance of an urgent magnetic resonance imaging (MRI) of the brain is indicated to confirm the clinical diagnosis of encephalitis [36].…”
Section: Encephalitismentioning
confidence: 99%